2020
DOI: 10.1126/sciadv.abc3851
|View full text |Cite
|
Sign up to set email alerts
|

Ancestry-dependent gene expression correlates with reprogramming to pluripotency and multiple dynamic biological processes

Abstract: Induced pluripotent stem cells (iPSCs) can be derived from differentiated cells, enabling the generation of personalized disease models by differentiating patient-derived iPSCs into disease-relevant cell lines. While genetic variability between different iPSC lines affects differentiation potential, how this variability in somatic cells affects pluripotent potential is less understood. We generated and compared transcriptomic data from 72 dermal fibroblast–iPSC pairs with consistent variation in reprogramming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 49 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…Case-control study designs (Design 1) are suited for this purpose, yet the clustering of data points introduced by obtaining multiple measurements from different genetically heterogeneous individuals has a considerable impact on the attainable statistical power. Previously, gene expression studies indicated that donorspecific differences account for a considerable proportion of the overall variability [21,[28][29][30][31][32][33][34]. Consequently, several studies conclude that iPSC-based studies benefit from including more donors, rather than more clonal iPSC lines from the same individual [21,22,29,31,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Case-control study designs (Design 1) are suited for this purpose, yet the clustering of data points introduced by obtaining multiple measurements from different genetically heterogeneous individuals has a considerable impact on the attainable statistical power. Previously, gene expression studies indicated that donorspecific differences account for a considerable proportion of the overall variability [21,[28][29][30][31][32][33][34]. Consequently, several studies conclude that iPSC-based studies benefit from including more donors, rather than more clonal iPSC lines from the same individual [21,22,29,31,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…IMR-90 (human fetal lung fibroblast) cells were obtained from the Coriell Institute for Medical Research and authenticated using Short Tandem Repeat (STR) analysis ( Capes-Davis et al., 2013 , American Type Culture Collection Standards Development Organization Workgroup et al., 2011 ). Primary dermal fibroblasts (White female, age 21; White male, age 21; Black female, age 21; Black male, age 22) are derived from an established cohort of previously characterized primary dermal fibroblasts at the National Institute of Environmental Health Sciences ( Mackey et al., 2018 ; Bisogno et al., 2020 ). Both IMR-90 and dermal fibroblasts were maintained in Dulbecco’s Modified Eagle Medium (DMEM) without phenol red and supplemented with 15% fetal bovine serum (FBS), high glucose, L-glutamine, sodium pyruvate, non-essential amino acids, and Antibiotic-Antimycotic.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed methods are provided in the online version of this paper and include the following: (Mackey et al, 2018;Bisogno et al, 2020). Both IMR-90 and dermal fibroblasts were maintained in Dulbecco's Modified Eagle Medium (DMEM) without phenol red and supplemented with 15% fetal bovine serum (FBS), high glucose, L-glutamine, sodium pyruvate, non-essential amino acids, and Antibiotic-Antimycotic.…”
Section: Star+methodsmentioning
confidence: 99%
“…iPSCs are autologous somatic cells that are reprogrammed into an embryonic-like stage in vitro. Two key features of human iPSCs are the capacity for self-renewal and pluripotency, which is the ability to differentiate into all cell types (Takahashi and Yamanaka, 2006;Yu et al, 2007), including HSCs (Bisogno et al, 2020;Demirci et al, 2020). Therefore, human iPSCs derived from patients are an attractive cell source for the development of novel strategies for the treatment of hematological disorders (Donada et al, 2020;Kennedy et al, 2012) (Figure 2A).…”
Section: Prospective Approaches For β-Thalassemia Treatmentmentioning
confidence: 99%